Identification of the L-menthol binding site in guinea-pig lung membranes - Wright, C E (1998)
1. L-Menthol inhibits both neurokinin A and capsaicin-induced bronchoconstriction in the guinea-pig and relaxes pre-constricted guinea-pig isolated bronchi. Structure-activity relationships have been defined for the action of (−)-menthol and related compounds on cold receptors, suggesting an action of L-menthol at a pharmacological receptor. We have performed radioligand binding studies to characterize the binding sites for [(3)H]-L-menthol in whole cell membranes prepared from guinea-pig lung tissue. 2. In kinetic studies, [(3)H]-L-menthol was found to bind rapidly and reversibly. Binding of [(3)H]-L-menthol to lung membranes was found to be time-dependant becoming fully associated to its site within 40 min, and half-maximum association occurred within 8 min (t(1/2)=8 min). [(3)H]-L-menthol was fully dissociated from its binding site within 8 min, (t(1/2)=2 min). 3. Inhibition studies presented a pharmacological profile of the ‘L-menthol site'. Capsaicin, capsazepine, D-menthol, eugenol, SCH23390 and camphor were all found to displace [(3)H]-L-menthol binding. In contrast WS3, noradrenaline, 5-hydroxytryptamine, spiperone, flunarazine, bepridil and nicardipine were without effect. 4. We have identified a L-menthol binding site in the guinea-pig, which may represent a site common to a variety of compounds.